Incidence of various physical disabilities amongst children - Ansari, Ali Muhammad (Journal of Postgraduate Medical Institute, 2011)
A survey has been conducted by a team of doctors and social workers of the department to assess the various causes of physical disabilities of the children who attend OPD clinics, rehabilitation clinics, orthopedic ward and in community. A proforma is used to record the finding. The preliminary result of this survey are presented with the hope that it will guide us in future both regarding preventive aspects and also steps that would help in the rehabilitation.